Implementation of Surgical Safety Checklist : Literature Review - Sudarsana, Sudarsana; Swarjana, I Ketut; Darmini, Yuliati; Dharmapatni, Ni Wayan Kesari (Jurnal Kesehatan Pasak Bumi Kalimantan, 2023)
Background: Health services provided to patients must not only be of high quality but also appropriate and prioritize patient safety, including patients undergoing surgery in hospitals. WHO in 2007 has provided recommendations for using a surgical safety checklist    (SSC) to improve patient outcomes. However, its application in the operating room is influenced by many factors and is still a challenge for surgeons, anesthesiologists and for nurses in filling out the SSC. Therefore, it is very important to conduct a literature  study to be able to find and describe previous studies that have been published, so that the results of this literature review can contribute to the implementation of SSC filling for the better. Methods:  This literature  study used 2 databases and from other sources. The search results found that there were 123 articles from Pubmed data based, 94 articles from Science Direct and there were 15 articles from other sources. However, only 12 articles were eligible for further review (included). Results: the literature  study found that the compliance of SSC filling was around 67% to almost 100%. Some of the barriers in implementing SSC filling are: lack of initiative, lack of support from senior surgeons and weak teamwork. Conclusion: educational intervention is very effective in improving SSC completion compliance.Keywords: Surgical safety checklist  , Hospital